Pleiotropy in the Genetic Predisposition to Rheumatoid Arthritis: A Phenome‐Wide Association Study and Inverse Variance–Weighted Meta‐Analysis. Issue 9 (6th August 2020) - Kawai, Vivian K.; Shi, Mingjian; Feng, Qiping; Chung, Cecilia P.; Liu, Ge; Cox, Nancy J.; Jarvik, Gail P.; Lee, Ming T. M.; Hebbring, Scott J.; Harley, John B.; Kaufman, Kenneth M.; Namjou, Bahram; et al.
Abstract : Objective: This study was undertaken to investigate the hypothesis that a genetic predisposition toward rheumatoid arthritis (RA) increases the risk of 10 cardiometabolic and autoimmune disorders previously associated with RA in epidemiologic studies, and to define new genetic pleiotropy present in RA. Methods: Two approaches were used to test our hypothesis. First, we constructed a weighted genetic risk score (wGRS) and then examined its association with 10 prespecified disorders. Additionally, a phenome‐wide association study (PheWAS) was carried out to identify potential new associations. Second, inverse variance–weighted regression (IVWR) meta‐analysis was used to characterize the association between genetic susceptibility to RA and the prespecified disorders, with the results expressed as odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: The wGRS for RA was significantly associated with type 1 diabetes mellitus (DM) (OR 1.10 [95% CI 1.04–1.16]; P = 9.82 × 10 −4 ) and multiple sclerosis (OR 0.82 [95% CI 0.77–0.88]; P = 1.73 × 10 −8 ), but not with other cardiometabolic phenotypes. In the PheWAS, wGRS was also associated with an increased risk of several autoimmune phenotypes including RA, thyroiditis, and systemic sclerosis, and with a decreased risk of demyelinating disorders. In the IVWR meta‐analyses, RA was significantly associated with an increased risk of type 1 DM ( P = 1.15 × 10 −14 ), with evidence of horizontal pleiotropy (Mendelian Randomization–Egger intercept estimate P = 0.001) likely driven by rs2476601, a PTPN22 variant. The association between type 1 DM and RA remained significant ( P = 9.53 × 10 −9 ) after excluding rs2476601, with no evidence of horizontal pleiotropy (intercept estimate P = 0.939). RA was also significantly associated with type 2 DM and C‐reactive protein levels. These associations were driven by variation in the major histocompatibility complex region. Conclusion: This study presents evidence of pleiotropy between the genetic predisposition to RA and associated phenotypes found in other autoimmune and cardiometabolic disorders, including type 1 DM.